2022
DOI: 10.1021/acsestwater.1c00387
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of RT-qPCR and RT-dPCR Platforms for the Trace Detection of SARS-CoV-2 RNA in Wastewater

Abstract: We compared reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and RT digital PCR (RT-dPCR) platforms for the trace detection of SARS-CoV-2 RNA in low-prevalence COVID-19 locations in Queensland, Australia, using CDC N1 and CDC N2 assays. The assay limit of detection (ALOD), PCR inhibition rates, and performance characteristics of each assay, along with the positivity rates with the RT-qPCR and RT-dPCR platforms, were evaluated by seeding known concentrations of exogenous SARS-CoV-2 in wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 60 publications
1
55
0
Order By: Relevance
“…PCR platform could impact measured SARS-CoV-2 concentrations due to differences between quantification methods and limits of detection. 8 , 21 Calculated ALOD values for N1 and N2 uniplex and duplex RT-qPCR assays were 21.8 and 24.8 copies/reaction, which are around 6–7 times greater than the probabilistic ALOD determined by the Poisson distribution (3 copies/reaction) and ∼20 times greater than the theoretical ALOD (1 copy/reaction). 15 Our ALODs for uniplex and duplex N2 are comparable to the uniplex RT-qPCR N2 ALOD (26.7 copies/reaction) but our N1 ALOD is higher than the N1 ALOD value (9.5 copies/reaction) previously reported.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…PCR platform could impact measured SARS-CoV-2 concentrations due to differences between quantification methods and limits of detection. 8 , 21 Calculated ALOD values for N1 and N2 uniplex and duplex RT-qPCR assays were 21.8 and 24.8 copies/reaction, which are around 6–7 times greater than the probabilistic ALOD determined by the Poisson distribution (3 copies/reaction) and ∼20 times greater than the theoretical ALOD (1 copy/reaction). 15 Our ALODs for uniplex and duplex N2 are comparable to the uniplex RT-qPCR N2 ALOD (26.7 copies/reaction) but our N1 ALOD is higher than the N1 ALOD value (9.5 copies/reaction) previously reported.…”
Section: Discussionmentioning
confidence: 84%
“…Since wastewater surveillance was used for monitoring COVID-19 from the start of the pandemic, 4 , 5 methodologies have varied greatly. 6 8 Numerous research groups have demonstrated that SARS-CoV-2 in wastewater reflects trends in community-level COVID-19 dynamics, and some reports observe that wastewater trends precede those of clinical reports. 1 , 9 Molecular-based wastewater surveillance depends on many factors, such as molecular processing methods (e.g., concentration and extraction of viral RNA), biochemical and microbiological complexity of wastewater matrix that can cause inhibition of molecular analyses, residence time in the sewer system, composite sampling duration and frequency, upstream sample processing methods, and virus recovery.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main advantages of the RT-dPCR over the RT-qPCR are its non-reliance on the calibration curve for direct absolute quantification, and reduced effects of PCR inhibitors [ 29 ]. Greater analytical sensitivity was observed in the RT-dPCR for the detection of SARS-COV-2 in clinical samples [ 30 ] and in wastewater samples [ 9 , 18 , 19 ]. In the study by Ref.…”
Section: Improvements In Pcr-based Methodsmentioning
confidence: 99%